Levantamento de condições de saúde de alunos dos estabelecimentos de ensino primário da Secretaria dos Negócios da Educação do Governo do Estado, no município de São Paulo Brasil Survey of the health conditions of elementary school children from the State elementary schools in São Paulo City, Brazil - Emilia Castejón Rodrigues; Gustavo Adolpho Coelho de Souza; Wilson Antonio Martins; Isaac Soibelman; Affonso Renato Meira; Norma Corte Faustino; Ana Rosa Ferreira Prado (Universidade de São Paulo, 1972)
Fez-se um levantamento das condições de saúde de escolares primários do município de São Paulo. Nos alunos componentes da amostra foram realizados os seguintes exames: exame físico geral; exame físico especial; exame de fezes. Os resultados obtidos no exame físico geral permitiram construir tabelas de peso e altura para crianças de ambos os sexos, de 7 a 14 anos. Foi verificada a presença de parasitoses intestinais em 89,4% dos escolares examinados. Concluiu-se que, ao nível de significância de 1%, existe associação entre ausência de saneamento básico nas residências dos escolares e a presença de parasitos intestinais nos exames de fezes. A survey about the health conditions of the elementary schools children of São Paulo City, was realized. The sample students were submitted to general and specialized physical examinations and to parasitological examination of feces. Tables of height and weight of boys and girls, aged 7-14 years, were built based on the general physical examination data. The results of the physical specialized examinations were compared with bibliographical data, whenever existed. About feces examinations, 89,4% of the school children selected presented parasites. At 1% of significance level, it was possible to accept that there was correlation between lackness of sanitation in the school children houses and the presence of intestinal parasites in the feces examination.